2015
DOI: 10.1118/1.4928602
|View full text |Cite
|
Sign up to set email alerts
|

Correction factor measurements for multiple detectors used in small field dosimetry on the Varian Edge radiosurgery system

Abstract: The commercial scintillating fiber, which produces accurate and consistent ratios of dose to water for nonstandard fields, can be used to measure correction factors for various detectors used in a clinical setting. This can allow for comparison of measured correction factors to previously published values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 48 publications
4
40
0
2
Order By: Relevance
“…In addition the differences between accelerator manufacturers, as well as different models produced by the same vendor, can contribute to different energy spectra, even if mechanical components are the same. Tanny et al (25) reported a kQitalicclin,Qitalicmsrfitalicclin,fitalicmsr correction factor study using multiple detectors, including the Edge diode detector, for Varian TrueBeam with flattening filter‐free energies of 6 MV (6 MV‐FFF) and 10 MV (10 MV‐FFF). Measurements of square field sizes from 6×6mm2 to 5×5cm2 with the Edge detector were compared to measurements from Exradin W1 scintillating fiber optic dosimeter manufactured by Standard Imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition the differences between accelerator manufacturers, as well as different models produced by the same vendor, can contribute to different energy spectra, even if mechanical components are the same. Tanny et al (25) reported a kQitalicclin,Qitalicmsrfitalicclin,fitalicmsr correction factor study using multiple detectors, including the Edge diode detector, for Varian TrueBeam with flattening filter‐free energies of 6 MV (6 MV‐FFF) and 10 MV (10 MV‐FFF). Measurements of square field sizes from 6×6mm2 to 5×5cm2 with the Edge detector were compared to measurements from Exradin W1 scintillating fiber optic dosimeter manufactured by Standard Imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, for 10 MV, the Edge output factors are significantly lower than MC results for cone diameters of 7.5 mm and less. One possible source of error which may explain this is that the correction factors for 4 mm and 5 mm were extrapolated from data by Tanny et al (25) and not actually measured. Another possible source of error is the different measurement conditions utilized by our study, relative to the one by Tanny and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…The results are compared with those obtained with other detectors we already use for small photon beam dosimetry, contributing to complement data that can be found in the literature, 24,[27][28][29] in particular regarding the behaviour of these detectors in smallfield beam dosimetry required for TPS commissioning (PDD, dose profile and OF measurements).…”
Section: Introductionmentioning
confidence: 90%
“…The output correction factor takes into account all the small‐field effects that have an impact on the output factor, such as partial volume averaging, atomic number, density and detector shielding. The new formalism was followed by a series of scientific papers providing numerical values of the correction factors for several beam quality, field size and detector combinations . Correction factors for most available radiotherapy and radiosurgery techniques (e.g., linear accelerators, CyberKnifes and Gamma Knifes) and modern radiation detectors (e.g., ionization chambers and solid‐state detectors) can be found in the cited papers.…”
Section: Introductionmentioning
confidence: 99%